A comparison of the resection rate for cold and hot snare polypectomy for 4–9 mm colorectal polyps: a multicentre randomised controlled trial (CRESCENT study). Issue 11 (28th September 2017) - Kawamura, Takuji; Takeuchi, Yoji; Asai, Satoshi; Yokota, Isao; Akamine, Eisuke; Kato, Minoru; Akamatsu, Takuji; Tada, Kazuhiro; Komeda, Yoriaki; Iwatate, Mineo; Kawakami, Ken; Nishikawa, Michiko; et al.
Abstract : Objective: To investigate the success rate of cold snare polypectomy (CSP) for complete resection of 4–9 mm colorectal adenomatous polyps compared with that of hot snare polypectomy (HSP). Design: A prospective, multicentre, randomised controlled, parallel, non-inferiority trial conducted in 12 Japanese endoscopy units. Endoscopically diagnosed sessile adenomatous polyps, 4–9 mm in size, were randomly assigned to the CSP or HSP group. After complete removal of the polyp using the allocated technique, biopsy specimens from the resection margin after polypectomy were obtained. The primary endpoint was the complete resection rate, defined as no evidence of adenomatous tissue in the biopsied specimens, among all pathologically confirmed adenomatous polyps. Results: A total of 796 eligible polyps were detected in 538 of 912 patients screened for eligibility between September 2015 and August 2016. The complete resection rate for CSP was 98.2% compared with 97.4% for HSP. The non-inferiority of CSP for complete resection compared with HSP was confirmed by the +0.8% (90% CI −1.0 to 2.7) complete resection rate (non-inferiority p<0.0001). Postoperative bleeding requiring endoscopic haemostasis occurred only in the HSP group (0.5%, 2 of 402 polyps). Conclusions: The complete resection rate for CSP is not inferior to that for HSP. CSP can be one of the standard techniques for 4–9 mm colorectal polyps. (Study registration: UMIN000018328)